The role of epistatic interactions underpinning resistance to parasitic Varroa mites in haploid honey bee (Apis mellifera) drones. (17th April 2018) - Conlon, Benjamin H.; Frey, Eva; Rosenkranz, Peter; Locke, Barbara; Moritz, Robin F. A.; Routtu, Jarkko
Abstract: The Red Queen hypothesis predicts that host–parasite coevolutionary dynamics can select for host resistance through increased genetic diversity, recombination and evolutionary rates. However, in haplodiploid organisms such as the honeybee ( Apis mellifera ), models suggest the selective pressure is weaker than in diploids. Haplodiploid sex determination, found in A. mellifera, can allow deleterious recessive alleles to persist in the population through the diploid sex with negative effects predominantly expressed in the haploid sex. To overcome these negative effects in haploid genomes, epistatic interactions have been hypothesized to play an important role. Here, we use the interaction between A. mellifera and the parasitic mite Varroa destructor to test epistasis in the expression of resistance, through the inhibition of parasite reproduction, in haploid drones. We find novel loci on three chromosomes which explain over 45% of the resistance phenotype. Two of these loci interact only additively, suggesting their expression is independent of each other, but both loci interact epistatically with the third locus. With drone offspring inheriting only one copy of the queen's chromosomes, the drones will only possess one of two queen alleles throughout the years‐long lifetime of the honeybee colony. Varroa, in comparison, completes its highly inbred reproductive cycle in a matter of weeks, allowing it to rapidly evolve resistance. Faced with the rapidly evolving Varroa, a diversity of pathways and epistatic interactions for the inhibition of Varroa reproduction could therefore provide a selective advantage to the high levels of recombination seen in A. mellifera . This allows for the remixing of phenotypes despite a fixed queen genotype.